Gastric inflammatory pseudotumour secondary to Actinomyces hordeovulneris infection in a cat. Issue 1 (December 2015) - Pietra, Marco; Zanoni, Renato; Peli, Angelo; Brunetti, Barbara; Linta, Nikolina; Capitani, Ombretta; Spinella, Giuseppe
Abstract Background The authors report the first case of feline gastric actinomycosis associated with infection byActinomyces hordeovulneris . Case presentation A 4-year-old, neutered male, semi-feral European cat, with a 1 year history of chronic vomiting, was referred to the clinic. Abdominal ultrasound examination identified a hypoechoic focal transmural thickening with loss of normal wall layering and hyperechoic speckles at the gastric body. Initial gastroscopic examination showed a tumour-like gastric mass with an ulcerated depression at the level of the greater curvature. Histologic examination of endoscopic biopsy specimens was consistent with a severe lymphoplasmacytic gastritis. After 2 months, due to persistence of abdominal discomfort, surgical exploration and intraoperative sampling of gross abnormalities was recommended. Full thickness gastric wall biopsies, and fine needle aspiration of the gastric thickening and gastric lymph node, were performed. Histopathological examination identified a transmural pyogranulomatous gastritis. Aspirate samples of the gastric wall cultured positive, with colony morphology, biochemical testing and PCR of the 16 s rRNA gene compatible withActinomyces hordeovulneris . After 4 months of treatment with cefovecin (8 mg/kg subcutaneously every 14 days), the vomiting completely resolved, as well as the ultrasonographic gastric alteration. Conclusion This case report of feline gastric actinomycosis, caused byActinomyces hordeovulneris, suggests that gastric bacterial infection should be considered in cases of focal gastric wall thickening associated with chronic vomiting in the cat, which may otherwise closely resemble neoplastic disease. Once a diagnosis of actinomycosis was obtained, a correct treatment with antibiotic therapy can resolve it.